Highly Stable Aqueous Zinc Metal Batteries Enabled by an Ultrathin Crack‐Free Hydrophobic Layer with Rigid Sub‐Nanochannels - Xu, Dongming; Ren, Xueting; Xu, Yan; Wang, Yijiang; Zhang, Shibin; Chen, Benqiang; Chang, Zhi; Pan, Anqiang; Zhou, Haoshen (Advanced science, 2023)
Aqueous zinc‐metal batteries (AZMBs) have received tremendous attentions due to their high safety, low cost, environmental friendliness, and simple process. However, zinc‐metal still suffer from uncontrollable dendrite growth and surface parasitic reactions that reduce the Coulombic efficiency (CE) and lifetime of AZMBs. These problems which are closely related to the active water are not well‐solved. Here, an ultrathin crack‐free metal–organic framework (ZIF‐7 x ‐8) with rigid sub‐nanopore (0.3 nm) is constructed on Zn‐metal to promote the de‐solvation of zinc‐ions before approaching Zn‐metal surface, reduce the contacting opportunity between water and Zn, and consequently eliminate water‐induced corrosion and side‐reactions. Due to the presence of rigid and ordered sub‐nanochannels, Zn‐ions deposits on Zn‐metal follow a highly ordered manner, resulting in a dendrite‐free Zn‐metal with negligible by‐products, which significantly improve the reversibility and lifespan of Zn‐metals. As a result, Zn‐metal protected by ultrathin crack‐free ZIF‐7 x ‐8 layer exhibits excellent cycling stability (over 2200 h) and extremely‐high 99.96% CE during 6000 cycles. The aqueous PANI‐V 2 O 5 //ZIF‐7 x ‐8@Zn full‐cell preserves 86% high‐capacity retention even after ultra‐long 2000 cycles. The practical pouch‐cell can also be cycled for more than 120 cycles. It is believed that the simple strategy demonstrated in this work can accelerate the practical utilizations of AZMBs.